Reconsideration of the optimal minimum lymph node count for young colon cancer patients: a population-based study - Xu Guan (BMC Cancer, 2018)
Abstract Background Currently, young colon cancer (CC) patients continue to increase and represent a heterogeneous patient group. The aim of this study was to explore the optimal minimum lymph node count after CC resection for young patients. Methods We performed a comprehensive search of the Surveillance, Epidemiology, and End Results (SEER) database, 2360 CC patients aged from 20 to 40 were analyzed. X-tile was used to determine the optimal cut-off point of lymph node based on survival outcomes of young patients. The cancer specific survival (CSS) was estimated with Kaplan-Meier method, the Cox proportional hazards regression model was used to analyse independent prognostic factors and exact 95% confidence intervals (CIs). Results Using X-tile analysis, 22-node measure was identified as the optimal choice for CC patients aged < 40. The 5-year CSS were 85.8% and 80.9% for patients examining ≥22 nodes and < 22 nodes. Furthermore, we identified that examining < 22 nodes was an independent adverse prognostic factor in patients aged < 40. In addition, the revised 22-node measure could examine more positive nodes than the standard 12-node measure in young patients. Conclusions For young colon cancer patients, the lymph node examination should be differently evaluated. We suggest that 22-node measure may be more suitable for CC patients aged < 40. Trial registration Retrospectively registered.